Knowledge and Opinion about Rights. Law and the Constitution of Individual Agency - Guibentif, P. (Representing Law - 2024 Annual Meeting of ISA Research Committee on Sociology of Law, 2024)
The Project of a Democratic Society as a Starting Point - Rights as a Device for Democratic Societies - Science as Part of a Democratic Society - Our Own Scientific Community as a Laboratory for the Study of the Role of Rights and their Knowledge in a Democratic Society